Membangun Sistem Integritas Untuk Pemberantasan Korupsi Dalam Sistem Peradilan Pidana Indonesia - Masyhudi Masyhudi (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This  research  aims  to  analyse  and  observe:  first,  the current  system  of corruption  eradication in  the Indonesia's positive law perspective; second, the strategy of the Indonesian government to eradicate the  corruption  in  future;  and  third,  the  concept  of  an  Integrity  System  to  eradicate  the  corruption  ininvestigations conducted by the Prosecutors, Police and KPK in Indonesia. The research method used is normative juridical legal research using a legal and conceptual approach. The results of the study showed that first, the system of corruption eradication  in Indonesian positive law currently has placed KPK as a leader, causing disharmony among the law enforcers; second, the Indonesian government's strategy to eradicate corruption in the future can be done through an integrity system within the scope of  the  KPK,  the  Police  and  the  Prosecutor's  Office;  third,  the  concept  of  the  Integrity  System  for corruption in investigation by the Attorney General's Office, the Police and the Corruption Eradication Commission  is  carried  out  by  establishing  the  Integrity  Court.  This  integrity  system  must  be  able  to position the three institutions as the independent Anti-Corruption Bodies.